Inhibition of the NF-κB and p38 MAPK pathways by scopoletin reduce the inflammation caused by carrageenan in the mouse model of pleurisy. (2nd September 2016) - Pereira dos Santos Nascimento, Marcus Vinicius; Arruda-Silva, Fábio; Gobbo Luz, Ana Beatriz; Baratto, Bruna; Venzke, Dalila; Mendes, Beatriz Garcia; Fröde, Tânia Silvia; Geraldo Pizzolatti, Moacir; Dalmarco, Eduardo Monguilhott
Abstract: Natural products have long been used worldwide as therapeutic agents, but it is only recently, in response to the new challenges posed by global population aging, that interest in research into potentially therapeutic natural products has reemerged. In this context, coumarins, chemical compounds found in plants that have known anti-inflammatory activity, are promising candidates for the development of new drugs. In this study we test the effect of scopoletin, a coumarin found in several plant species, on carrageenan-induced inflammation in the mouse model of pleurisy. Initially, the effects of scopoletin on leukocyte migration and exudate concentrations were evaluated at three different doses (0.1, 1 and 5 mg/kg) and time (0.5–4 h before pleurisy). In the next step, we chose the lowest dose capable of inhibiting the inflammatory parameters (1 mg/kg), in order to analyze the myeloperoxidase and adenosine deaminase activities, the nitric oxide, tumor necrosis factor-α, and interleukin 1β levels in the fluid leakage, and the p65 subunit of NF-κB and p38 MAPK phosphorylation. Scopoletin at a dose of 1 mg/kg was able to significantly reduce cell migration and exudation to the pleural fluid ( p < 0.01). Scopoletin at the same dose also decreased the myeloperoxidase and adenosine-deaminase activities and nitric oxide, tumor necrosis factor-α, and interleukin-1β levels ( p < 0.01). In addition, it significantly reduced p65 and p38 phosphorylation in the mouse lungs ( p < 0.01). Our results reinforce that scopoletin has important anti-inflammatory activity, and shows, that this effect can be attributed to the ability of this compound to inhibit the phosphorylation of NF-κB and p38 MAPK.